PELAKSANAAN LITERASI DAN NUMERASI PADA KURIKULUM MERDEKA DI SD NEGERI 173/IX RANTAU HARAPAN - Nenden Nuraini Rizkiah; Destrinelli; Akhmad Faisal Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research method used by the author is qualitative with a phenomenological approach. The subjects of the study are teachers and students at SDN 173/IX Rantau Harapan who are involved in the implementation of literacy and numeracy activities in the Independent Curriculum. Data collection techniques through observation, interviews, and documentation. Analysis techniques include data reduction, data presentation, and conclusion drawn. Based on the results of the research, the implementation of literacy and numeracy in SD Negeri 173/IX Rantau Harapan using the Independent Curriculum shows an improvement in student ability, although there are still challenges. Literacy activities are carried out through various methods such as reading together, group discussions, and the use of diverse reading materials to improve student understanding. Meanwhile, numeracy activities are applied with a practice-based approach, such as calculation in the context of daily life and educational games to strengthen the understanding of mathematical concepts. School report cards in literacy and numeracy activities show significant development and improvement. This increase can be seen from the 2024 SDN 173/IX Rantau Harapan education report report. In the report, it can be seen that the change in the value of literacy and numerical achievement from last year has increased. The increase in literacy was 13.33% from 86.67% in 2023, an increase of 100%. Meanwhile, the increase in numeracy achievement value was 36.30%, which initially in 2023 was in the range of 60% numeracy ability, increasing by 96.3% in 2024. It is hoped that the implementation of literacy and numeracy can be more effective in supporting the achievement of the goals of the Independent Curriculum in improving the basic competencies of students as a whole.